Developing RME-based module in statistics to improve problem-solving skills for higher education students - Susanto, Edi; Susanta, Agus; Aliyyah Irsal, Nur; Stanggo, Pratiwi Disha (Universitas Hamzanwadi, 2024)
In university learning, it is important to use learning resources that can facilitate students' thinking skills. So it is necessary to develop teaching materials for learning material in class, So it is necessary to develop teaching materials that can help students understand the concepts of the material. This research aims to develop a statistics teaching module based on a realistic mathematical approach to foster student problem-solving. This research and development uses a 4-D model in four stages, namely: definition, design, development, and dissemination. Product trials are carried out in three stages, namely: a validity test, a limited test, and a wide-scale test. The test subjects in this research were students from the mathematics education study program at three universities in Bengkulu. The research instruments were questionnaire sheets and problem-solving tests on basic statistical material. The research results show that the RME statistics teaching module meets the criteria of being valid, practical, and effective in terms of students' problem-solving abilities. The suggestion from the research results is that it is important to present a context that is relevant to the student's environment in the use of RME teaching materials.